Developing the Kanga’s Escape Learning Model with Box Modifications for Upper Grade Students - Mohamat Luthfi Widjayanto; Agus Widodo Suripto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aimed to develop and evaluate the feasibility, practicality, and effec-tiveness of the Kanga Es Cape learning model, a Kids Athletics-based jumping game using modified box media, for upper-grade elementary school students. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. Product validation involved one game expert and two Physical Education practitioners. Small-group trials were conducted with 14 students from SDN Pakintelan 03, while large-group trials involved 30 students from SDN Pakintelan 02 and SDN Pakintelan 03. Data were collected through question-naires, observations, interviews, and pretest-posttest assessments. Expert vali-dation results indicated that the product was categorized as feasible and highly usable. Small-group and large-group trials also showed high practicality ratings. Effectiveness testing demonstrated significant improvements in students’ learn-ing outcomes, with mean cognitive scores increasing from 32.20 to 68.97, affective scores from 31.07 to 64.47, and psychomotor scores from 35.83 to 63.33 (p < 0.001). Therefore, the Kanga Es Cape learning model is feasible, practical, and effective for supporting active participation and movement skill development in elemen-tary school physical education learning.